TORTOR MANILPOKKON HASAYA DALAM UPACARA ADAT HORJA GODANG DI KABUPATEN TAPANULI SELATAN TERHADAP BENTUK PENYAJIAN - ida marohana nasution (Universitas Negeri Medan, 2014)
This research is a study about Tor-tor Manilpokkon Hasaya in Horja Godang Ceremony from South Tapanuli Society Against Presentation Form. The purpose of this study was to describe the form of presentation and meaning of Tor- tor Manilpokkon symbols this Hasaya. In the results of this study the authors used several theories that support the research topics include the theory of form, meaning theory, the theory of symbols, the meanning of Tor to r, system theory and the meanning of traditional ceremonies. The time which used in this study to discuss about Tor-tor Hasaya Manilpokkon this for two months, start from July to Setember 2014. The research is in the village Wood Ombun South Tapanuli. The population in this study are some of the traditional leaders Angkola communities who lived in the Padangsidempuan city, organizing ceremonies, relatives and family as panortor. The sample in this stu dy are traditional leaders, some of traditional family or party organizers family. D ata collectiont echnique ar, interviews, literature study and documentation, and then analysis with qualitative methods . According to the research which have done can be seen that Tor-tor manilpokkon hasaya describes gratitude and thanks to the fine spirit for having launched their celebration.In tor-tor is no accompaniment lyrics devoted to this hasaya but the panortor said Bellak-lell ak that has meaning thanks to the fine spirit and manilpokkon hasaya (buffalo cutter) as its symbol. Keywords: Tor-tor Manilpokkon Hasaya